PREFERENSI Nezara viridula ORDO Hemiptera PADA BEBERAPA JENIS VARIETAS KEDELAI (Glycine max. L) - Irna Syofia; Faisal Amri (AGRIUM: Jurnal Ilmu Pertanian, 2013)
The aim of this research was to investigate the Soyben varieties that  damage inferior relative. This research utilize agglomerate Random Design (RACK) Factorial is with 2 factor those are analyzed which is N.viridula amount factor( K ), varietas's type factor (V ).  Conduct that at quiz as follows for N. viridula amount( K) and varietas's type( V ) by following conduct combines: KoV1= 0 / anjasmoro, K1V1 = 3 number / anjasmoro, K2V1 = 6 number / anjasmoro, K3V1 = 9 number / anjasmoro, and KoV2= 0 / grobongan, K1V2 = 3 number / grobongan, K2V2 = 6 number / grobongan, K3V2 = 9 number / grobongan, KoV3= 0 / kaba, K1V3 = 3 number / kaba,K2V3 = 6 number / kaba,  K3V3 = 9 number / kaba. Result observationaling to point out that supreme attack intensity N. Viridula available on varietas kaba which is as big as 6,17 % and bottom most on varietas anjasmoro which is as big as 5,56%. Application of  N. Viridula as much 9 number evoke highest attack intensity which is as big as 11,33%. Usufruct supreme Soybean on varietas anjasmoro without application N. Viridula  which is as big as 2.03 tons / ha whereas supreme result losses also on varietas anjasmoro with application N. Viridula  as much 9 numberKey word: N. Viridula,  attack intensity,  result, soybean